2020
DOI: 10.3390/ijerph17082744
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Upper Limb Injury in Tennis Players: A Systematic Review

Abstract: Studies in tennis injuries have successfully identified the incident rate, the location, and the type of the injury. The majority of the studies have multiple perspectives (epidemiology, biomechanics, performance), however only a few studies were able to identify risk factors or mechanisms that contribute to tennis injuries. Until now, there has not been a systematic literature review that identifies risk factors for tennis injuries. The objective of this review was to identify and critically appraise the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 47 publications
1
28
0
2
Order By: Relevance
“…Há importância no gerenciamento ideal da carga de treinamento, fazendo-se necessário quantificar a carga de treino e adaptá-la a cada atleta. A frequência das partidas esportivas e a intensidade do treinamento têm uma influência importante nos problemas do ombro, ampliando as lesões por esforço causadas por movimentos inadequados e falta de tempo de recuperação (Tooth, 2020;Moller, 2017;Kekelekis, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Há importância no gerenciamento ideal da carga de treinamento, fazendo-se necessário quantificar a carga de treino e adaptá-la a cada atleta. A frequência das partidas esportivas e a intensidade do treinamento têm uma influência importante nos problemas do ombro, ampliando as lesões por esforço causadas por movimentos inadequados e falta de tempo de recuperação (Tooth, 2020;Moller, 2017;Kekelekis, 2020).…”
Section: Discussionunclassified
“…Ao analisar os fatores de riscos potenciais para causar lesão de membro superiores em tenistas pode-se observar que os principais são: tênis prolongado, discinesia escapular, fadiga muscular, propriedades escapulotorácicas, cinemática do ombro, nível de habilidade e técnica. Os tenistas com discinese escapular tendem a apresentar redução do escapo subacromial, a discinesia escapular pode reduzir o espaço subacromial, embora as evidências para isso sejam confusas, também pode reduzir a força do manguito rotador, essa pode prejudicar o controle motor, resultando na translação superior e posterior da cabeça do úmero gerando um desgaste mecânico das estruturas do espaço subacromial (Kekelekis, 2020;Hickey, 2017).…”
Section: Discussionunclassified
“…Traumas to the shoulder joint are very frequent in professional tennis players, mainly due to the repetitive mechanical overload of the shoulder joint. Shoulder pain was present in 24% of top tennis players with ages comprised between 12 and 19 years old (9). Muscle misalignment caused by repetitive unilateral movements (15) that cause stress on fascial tissues, intervertebral discs, spinal ligaments and not only.…”
Section: Introductionmentioning
confidence: 99%
“…(21)In this review, 68 questionnaires were completed by top Slovenian athletes. Of which 29 are table tennis players and 39 tennis players.The average age of questioned athletes was 19.37 years (9).…”
mentioning
confidence: 99%
“…12 In overhead sports, shoulder injuries and shoulder pain pose substantial problems for athletes, and several studies have presented a variety of risk factors such as decreased shoulder strength, range of motion deficits, and scapular dyskinesia that increase the risk of these complaints. 6,28,31,38,40,43,44 Based on previous research (ie, cross-sectional data, prospective studies, and systematic reviews), shoulder injuries have been identified as one of the most common in young tennis players, 1,2,13,15,19,25,29,37,41 with an incidence of 2.6 to 3.6 injuries per 1000 hours played. 17 Over the past decade, the acute:chronic workload ratio (ACWR) and its association with noncontact and contact injuries has been extensively investigated.…”
mentioning
confidence: 99%